Using Self-Efficacy to Assess the Readiness of Nursing Educators and Students for Mobile Learning - Kenny, Richard F.; Van Neste-Kenny, Jocelyne M. C.; Burton, Pamela; Park, Caroline L.; Qayyum, Adnan (International Review of Research in Open and Distributed Learning, 2012)
The purpose of this study was to assess the self-efficacy of nursing faculty and students related to their potential use of mobile technology and to ask what implications this technology has for their teaching and learning in practice education contexts. We used a cross-sectional survey design involving students and faculty in two nursing education programs in a western Canadian college. In January, 2011, 121 faculty members and students completed the survey. Results showed a high level of ownership and use of mobile devices among our respondents. The median mobile self-efficacy score was 75 on a scale of 100, indicating that both faculty and students were highly confident in their use of mobile technologies and prepared to engage in mobile learning.